Prevalence and Developmental Profiles of Autism Spectrum Disorders in Children With Global Developmental Delay - Shan, Ling; Feng, Jun-Yan; Wang, Tian-Tian; Xu, Zhi-Da; Jia, Fei-Yong (Frontiers in Psychiatry, 2022)
Background: Previous studies have mostly explored the comorbidities of Global developmental delay (GDD) in children with Autism Spectrum Disorders (ASD) from the perspective of ASD. The study focus on the perspective of GDD to investigate the prevalence and developmental profiles of ASD in GDD and to explore the correlation between the developmental level and symptoms of autism. Methods: Clinical data of 521 children with GDD aged from 24 months to 60 months were retrospectively analyzed. Analyses were performed first for the whole sample and then subdivided into two subgroups (GDD+ASD-, GDD+ASD+) according to whether had ASD. Symptoms of autism were evaluated by the Autism Behavior Checklist and the Childhood Autism Rating Scale. The Chinese version of the Gesell Developmental Schedules was used to evaluate the level of children’s mental development. Result: The prevalence of ASD in children with GDD was 62.3%. The total average developmental quotient (DQ) of GDD was mildly deficient and was negatively correlated with symptoms of autism (p<0.05); language ability was severe and extremely severe deficient (P < 0.05). GDD+ASD- group and GDD+ASD+ group have some common points as well as differences in the developmental features. The language delay of children in both subgroups was the most obviously defected, thereafter followed by the item of personal social activity. In the GDD+ASD+ group, the DQ of gross motor skills＞fine motor skills＞adaptability (p<0.05). There were no significant differences among the DQ of gross motor skills, fine motor skills and adaptability in GDD+ASD- group (p>0.05). The GDD+ASD-group had better adaptability, fine motor skills, language ability, personal social activity than that of the GDD+ASD+ group, but the gross motor skills in GDD+ASD- group were worse (p<0.05). Conclusion: GDD children have a high proportion of comorbid ASD, and GDD children with poorer developmental levels are more likely to have ASD symptoms. Development profiles in both GDD+ASD- children and GDD+ASD+ children have common features but there are also differences. GDD+ASD+ group is worse than GDD+ASD- group in terms of the overall development level.